2021
DOI: 10.1155/2021/1487287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammasome Activation in Early HIV Infection

Abstract: The inflammasome pathway is an important arm of the innate immune system that provides antiviral immunity against many viruses. The main pathways involved in virus infections include the NLRP3, IFI16, and AIM2 pathways. However, a succinct understanding of its role in HIV is not yet well elucidated. In this review, we showed that NLRP3 inflammasome activation plays a vital role in inhibiting HIV entry into target cells via the purinergic pathway; IFI16 detects intracellular HIV ssDNA, triggers interferon I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Absent in melanoma 2 (AIM2) is a cytosolic sensor for double-stranded DNA (dsDNA) and tumor suppressor that is responsible for inflammasome activation and is involved in the host immune response to viruses and intracellular bacteria ( Saiga et al., 2012 ). AIM2 binds to HIV dsDNA and may trigger acute inflammation and pyroptosis ( Ekabe et al., 2021 ). Regarding the AIM2 rs2276405 polymorphism, to our knowledge, only one study showed a significant difference in the genotype frequencies of this Single Nucleotide Polymorphism (SNP) between individuals with and without TB in a Taiwanese population ( Liu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Absent in melanoma 2 (AIM2) is a cytosolic sensor for double-stranded DNA (dsDNA) and tumor suppressor that is responsible for inflammasome activation and is involved in the host immune response to viruses and intracellular bacteria ( Saiga et al., 2012 ). AIM2 binds to HIV dsDNA and may trigger acute inflammation and pyroptosis ( Ekabe et al., 2021 ). Regarding the AIM2 rs2276405 polymorphism, to our knowledge, only one study showed a significant difference in the genotype frequencies of this Single Nucleotide Polymorphism (SNP) between individuals with and without TB in a Taiwanese population ( Liu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Except for IL-1α, rate of biomarker decay appeared unaffected by time since EDDI at enrollment, and those who started treatment immediately had faster declines in only 3 other markers. Although we did not directly evaluate inflammasomes in this study, our findings hint at a complex regulation of acute inflammation that depended on time since HIV infection and exogenous exposures [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular PRRs that detect viral nucleic acids include the cytosolic DNA sensor cyclic guanosine adenosine synthase (cGAS) [106][107][108][109] and interferon-inducible protein 16 (IFI16) [110], and the cytosolic RNA sensors retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs), melanoma differentiation-associated protein 5 (MDA5) [111], and laboratory of genetics and physiology 2 (LGP2) [112]. Other PPRs that sense nucleic acids include a subset of Toll-like receptors (TLR-3, -7, -8, -9 and -13), and nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) [25,[113][114][115][116]. Furthermore, nucleic acids have been suggested to activate the NLRP1 inflammasome, cytokine expression and the pyroptosis of CD4+ T cells [25,[116][117][118][119].…”
Section: Hiv-1 Rnas Inducing Inflammatory Signalsmentioning
confidence: 99%